2018
DOI: 10.5562/cca3225
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Antimicrobial and Antiproliferative Activities of Synthesized 2,2,5,5-Tetramethyl-9-aryl-3,4,5,6,7,9-hexahydro-1H-xanthene-1,8(2H)-dione Derivatives

Abstract: Ten biologically active 2,2,5,5-tetramethyl-9-aryl-3,4,5,6,7,9-hexahydro-1H-xanthene-1,8(2H)-dione derivatives were synthesized and their structures were confirmed by IR, 1 H and 13 C NMR spectroscopy and mass spectrometry. Synthesized compounds were scanned for their antioxidant, antimicrobial and antiproliferative activity. Antibacterial activity was tested by the diffusion and dilution method against Bacillus subtilis, Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa, while antifungal acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 17 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…al. [6], and the 1,8-dioxo-octahydroxantene derivative compound substituted with hydroxyl group revealed in the study by our previous publication [7,13]. The study carried out by Nirwani et al [26] presented that the hydroxyl group could hinder the free radicals reaction continuity through the hydrogen radical donation to the free radicals by hydroxyl group homolytic reaction producing more stable and less reactive free radicals.…”
Section: Table 1 Gc-ms Analysis Of Synthesized Compounds Without Cata...mentioning
confidence: 96%
See 1 more Smart Citation
“…al. [6], and the 1,8-dioxo-octahydroxantene derivative compound substituted with hydroxyl group revealed in the study by our previous publication [7,13]. The study carried out by Nirwani et al [26] presented that the hydroxyl group could hinder the free radicals reaction continuity through the hydrogen radical donation to the free radicals by hydroxyl group homolytic reaction producing more stable and less reactive free radicals.…”
Section: Table 1 Gc-ms Analysis Of Synthesized Compounds Without Cata...mentioning
confidence: 96%
“…Research carried out by Zukic et al [6] mentioned that the 1,8-dioxo-octahydroxantene derivatives substituted with hydroxyl groups in the ortho position and methoxy group in the meta position toward the benzene ring had an antioxidant activity with 62.83% inhibition and EC50 of 0.13 mM. Another study conducted by Retnosari et al [7] identified that 1,8dioxo-octahydroxantene derivatives substituted with hydroxyl groups in the para position toward the benzene ring had an antioxidant activity with lC50 of < 2 ppm.…”
Section: Introductionmentioning
confidence: 99%
“…Acetyl vanillin compounds have also been shown to have bactericidal action [2]. When OH group are present, antibacterial action against Pseudomonas strains is boosted [15]. Piperidine has been associated to antibacterial, antifungal, anticancer, anticonvulsant, and antihyperlipidemic activities [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%